Effect of Irradiation on Quality of Vacuum-Packed Spicy Beef Chops - Liming Zhao; Yin Zhang; Siya Guo; Wei Xiong; Hu Xia; Wenlong Liu; Zhongli Pan; Chandrasekar Venkitasamy (Journal of Food Quality)
To develop an alternative pasteurization process for the spicy beef jerky (SBJ), it was treated with irradiation doses of 0, 0.5, 1.5, 3, 4, 6, and 8 kGy and the sensory attributes, texture properties, drip loss, and the protein biological efficiency were studied. The results showed that lightness, drip loss, and off-odor of SBJ increased, while the hardness, chewiness, gumminess, color preference, and taste of SBJ decreased with the increase in irradiation dose. This tendency was obvious as the irradiation dose increased to 6 kGy and 8 kGy. The possible reason for these quality changes might be due to the free radicals produced by irradiation. This speculation is supported by the decrease of the content of capsanthin and the increase of the content of TBARS of SBJ with the increase in irradiation dose. The plate counts of treated SBJ indicated that 4 kGy was suitable for pasteurization of SBJ.